Language Functions and Expressions Used in Handling Guest Complaints in Emails at New Sunari Lovina Beach Resort - Dewa Ayu Nita Damayanti; Anak Agung Sri Barustyawati; Putu Ayu Prabawati Sudana (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
Guest complaints were unavoidable in the hospitality industry, requiring appropriate language functions and expressions in handling guest complaints. This research aims to identify the language functions and expressions used to handle guest complaints in emails at the New Sunari Lovina Beach Resort. It focuses on how language functions and expressions are used. It used a qualitative document study, and data was collected through identification by taking multiple samples of complaint emails from New Sunari Lovina Beach Resort. This research showed that the staff at New Sunari Lovina Beach Resort used six types of language functions in responding to guest complaint emails, such as thanking, apologizing, giving a reason, offering something, suggesting, and showing sympathy. These language functions were realised through various language expressions in the staff's responses. From 18 emails, the data were grouped into eight representative cases due to similarities in the type of complaint and staff responses. This research contributed to examining the handling of guest complaints via email at New Sunari Lovina Beach Resort.